Calistung E-Module Innovation For Strengthening Basic Literacy and Numeracy Student - Mufidah Sufianti; Nurdyansyah (Jurnal Ilmiah Sekolah Dasar, 2023)
Calistung skills (reading, writing, arithmetic) must be mastered by students as the basis of literacy and numeracy. The lack of understanding of Calistung causes students to have difficulty understanding other subjects. This study aimed to develop and examine the feasibility, practicality, and effectiveness of the Calistung e-Module in strengthening students' basic literacy and numeracy. This research is a type of research and development (research and development) with the ADDIE model. Researchers collected data using questionnaires, document checklists, and documentation. The research subjects were class I students, totaling 30 students. Data analysis techniques are using descriptive qualitative analysis, quantitative, and inferential statistics. The results of the study, namely the validation test from media experts and learning design, obtained an average value of 3.6 (90%), which means it is very valid, while the material expert test and linguist test each was 3.75 (93.75%) with a very valid category. The product development practicality test obtained an average score of 3.89 (97.25%) in the very attractive category. The t-test results showed a significant increase in the average student learning outcomes after receiving a different treatment, namely using the Calistung e-Module. The listing e-module is a practical, interesting, and effective learning medium.